Market reactions towards the announcement of sukuk issuance: evidence from Malaysian market / Muzrifah Mohamed, Norliza Che Yahya and Nur Ashikin Ishak - Mohamed, Muzrifah; Che Yahya, Norliza; Ishak, Nur Ashikin (Research Management Institute (RMI), 2017)
One of the unique features of Malaysian financial market is the co-existence of Islamic bonds market or better known as sukuk market and the conventional bonds. Unlike conventional bonds, the Islamic bonds are structured to comply with Shariah principles, which prohibits the charging of riba' or interest. The history of sukuk market records Malaysia as one of the pioneering countries of Islamic bond products when it kicks off the global sukuk arena with the issuance of Shell MDS Sdn Bhd in 1990 ("Bloomberg Businessweek," 2013). The issuance of Shell MDS Sdn Bhd has been the spectator of the unprecedented proliferation for sukuk issuance especially after the global financial crisis in 2007-2008. The global financial crisis has alerted investors on the significance of other investment alternatives as a means to diversify and minimise the risk of their investment portfolio. To totally be dependent on the equity market might limit the investors' chance to optimise their portfolio return particularly during the economic downturn; sukuk is viewed as one of the best alternatives for risk diversification strategy. To date, sukuk is reported as the most active Islamic financial instrument issued in debt market and an important avenue for fundraising mechanism for companies and also as investment activities for investors. As depicted in Figure 1, even though the total number of global sukuk issuance experienced a temporary drop in the year 2008, it regained its momentum in 2009. The consistent growth of its size issued from year to year indicates that the global sukuk market is gradually developing. In other words, the debt market participants (e.g. firms and investors) have begun to recognise the significance of sukuk as an alternative investment channel. Further on the statistic, despite a decline in the total amount of sukuk issuance in 2008, Malaysia is still positioned as the largest sukuk market in the world during and after the financial crisis (Bank Negara Malaysia and Securities Malaysia, 2009).